Brown meets green: light and nutrients alter detritivore assimilation of microbial nutrients from leaf litter. Issue 6 (24th May 2021) - Price, Taylor L.; Harper, Jennifer; Francoeur, Steven N.; Halvorson, Halvor M.; Kuehn, Kevin A.
Abstract: In aquatic detrital‐based food webs, research suggests that autotroph‐heterotroph microbial interactions exert bottom‐up controls on energy and nutrient transfer. To address this emerging topic, we investigated microbial responses to nutrient and light treatments during Liriodendron tulipifera litter decomposition and fed litter to the caddisfly larvae Pycnopsyche sp. We measured litter‐associated algal, fungal, and bacterial biomass and production. Microbes were also labeled with 14 C and 33 P to trace distinct microbial carbon (C) and phosphorus (P) supporting Pycnopsyche assimilation and incorporation (growth). Litter‐associated algal and fungal production rates additively increased with higher nutrient and light availability. Incorporation of microbial P did not differ across diets, except for higher incorporation efficiency of slower‐turnover P on low‐nutrient, shaded litter. On average, Pycnopsyche assimilated fungal C more efficiently than bacterial or algal C, and Pycnopsyche incorporated bacterial C more efficiently than algal or fungal C. Due to high litter fungal biomass, fungi supported 89.6–93.1% of Pycnopsyche C growth, compared to 0.2% to 3.6% supported by bacteria or algae. Overall, Pycnopsyche incorporated the most C in high nutrient and shaded litter. Our findings affirm others' regarding autotroph‐heterotroph microbial interactions and extend into the trophic transfer of microbial energy and nutrients through detrital food webs.